Engineering multicellular living systems—a Keystone Symposia report. Issue 1 (30th September 2022) - Cable, Jennifer; Arlotta, Paola; Parker, Kevin Kit; Hughes, Alex J.; Goodwin, Katharine; Mummery, Christine L.; Kamm, Roger D.; Engle, Sandra J.; Tagle, Danilo A.; Boj, Sylvia F.; Stanton, Alice E.; Morishita, Yoshihiro; et al.
Abstract: The ability to engineer complex multicellular systems has enormous potential to inform our understanding of biological processes and disease and alter the drug development process. Engineering living systems to emulate natural processes or to incorporate new functions relies on a detailed understanding of the biochemical, mechanical, and other cues between cells and between cells and their environment that result in the coordinated action of multicellular systems. On April 3–6, 2022, experts in the field met at the Keystone symposium "Engineering Multicellular Living Systems" to discuss recent advances in understanding how cells cooperate within a multicellular system, as well as recent efforts to engineer systems like organ‐on‐a‐chip models, biological robots, and organoids. Given the similarities and common themes, this meeting was held in conjunction with the symposium "Organoids as Tools for Fundamental Discovery and Translation". Abstract : On April 3–6, 2022 experts in the field met at the Keystone symposium "Engineering Multi‐Cellular Living Systems" to discuss recent advances in understanding how cells cooperate within a multi‐cellular system, as well as recent efforts to engineer systems like organ‐on‐a‐chip models, biological robots, and organoids.